Contamination rate of commonly consumed fresh vegetables and fruits with parasites of medically importance in Wolkite and Butajira Towns of Gurage Zone, Southern Ethiopia - Fitsum Bekele; Teha Shumbej; Andamlak Dendir; Dereje Mesfin; Absra Solomon (International Journal of Public Health Science (IJPHS), 2020)
Intestinal parasitic infections are among the most common on causes  of disease in humans, responsible for considerable morbidity and mortality. Commonly consumed raw vegetables and fruits are among the ways through which humans become infected with parasites of medical importance. A prospective cross-sectional study with an aim of describing the parasite contamination rate of raw fresh vegetables and fruits sold at the central open-aired market of Butajira and Wolkite towns, in southern Ethiopia was conducted on a total of 270 fresh vegetable and fruits samples. Standardized parasitological techniques were employed to detect diagnostic stages of parasites.98 out of the 270 (36.3%) samples were found positive for intestinal parasites. Remarkably, twenty eight out of the forty five cabbage samples analyzed, 62.2%, were found to be contaminated with parasites of medical importance, registering the highest level of contamination. On the contrary Avocado was found to be the least contaminated produce with contamination rate of 17.7% (8/45). Significant association was observed between the kind of vegetables analyzed and existence of parasites (p=0.002). This study identified high rate of contamination in commonly consumed vegetables and fruits. The authors believe that the role fruits and vegetables paly in the transmission of intestinal parasitic infections to humans is un questionable. Substantial attention is needed from all relevant bodies to tackle this problem.